Conceptual Design of a Multifunctional CRM System for the Company Dines d.o.o. - Matjašič, Tilen; Vukovič, Goran; Rojc, Maja (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
The purpose of the chapter is to examine the need to develop and implement a CRM system for the company Dines d. o. o., which operates in the field of heating, cooling and ventilation, focusing exclusively on the sales module for effective communication with customers in the B2B segment. The research part is based on an in-depth qualitative interview with the company's sales manager, with which we identified the key needs and functionalities that the new system should contain. Based on the information collected, we designed the concept of the sales module and prepared a detailed implementation plan. The result of our research is a conceptual design of a CRM system that will enable more effective management of relationships with business customers and optimization of the company's sales processes. We provided recommendations for long-term use, maintenance and analysis of potential challenges during implementation. We conclude the thesis with findings on the importance of digitalization of sales activities and recommendations for the company's next steps.